A Quantitative Ranking of the Biomedical Informatics Serials - Sittig, D. F.; Kaalaas-Sittig, J. (Methods of Information in Medicine, 1995)
We have developed a quantitative serial ranking system based on multiple citation analysis techniques, library use statistics, expert opinion, and selected distinguishing publication characteristics. Evaluation criteria categories include: average Science Citation Index (Impact Factor, Immediacy Index, Total citations) rankings from 1987 to 1992; citation source counts of multiple “core” biomedical informatics publications; a questionnaire sent to American College of Medical Informatics Fellows; publication delay; distinguishing characteristics (e. g., subscription cost, total circulation, year established, places indexed, affiliation with a professional society, major biomedical resource library holdings); and the total number of interlibrary loan requests to the U. S. National Library of Medicine. The top serials were Computers and Biomedical Research, MD Computing, Methods of Information in Medicine, Medical Decision Making and Computers in Biology and Medicine.
Keywords: Citation Analysis; Bibliometrics; Medical Informatics; Collection Development; Serial Ranking